Studying Problems of Art Interpretation in Music at University of Culture - S. Yu. Lysenko (Высшее образование в России)
The necessity of scientific understanding of the problem of the classical heritage representation and interpretation in contemporary artistic practice has now become particularly relevant. There are certain difficulties in studying the problem of artistic interpretation closely connected with creation of categorical apparatus. It became clear that traditional Art studies using conventional conceptual system are not ready for up-to-date reading of the classical heritage and there are no clear criteria for assessment of the topical artistic solutions for classics, especially in musical theatre. The range of interpreters’ methods are rather wide – from authentic reconstructions to free stage variations and games with author’s meanings. In modern conditions the methodological apparatus of art studies should be revised, and accordingly the content of specialized courses for students of institutes and universities for Arts should be updated. It is apparent that postmodern discourse influences on the organization of the educational process and pedagogical technologies selection for teaching at educational institutions for Arts. The author views deconstruction not only as an art method but also as a research strategy for text analysis. Postmodern strategies orient pedagogues and students to use dialogue, permanent interpretation, multidimensional, uncompleted approaches to artistic products.